O polemică la sfârşitul secolului al XIX-lea: C. Stere versus A. A. Bădărău - Victor Durnea (Revista de Istorie și Teorie Literară)
The article relates a polemic between C. Stere – a socialist and A. A. Bădărău – member of the Conservative Party. The conflict began with a series of attacks launched by the conservative newspaper “Opinia” towards the liberal prime minister D. A. Sturdza, in which the Liberal Party was accused of making a short time electoral alliance with the socialists. Stere was denounced repeatedly as a political speculator.